Lily's Crossing - Giff, Patricia Reilly (New York : Delacorte Press, 1997)
During a summer spent at Rockaway Beach in 1944, Lily's friendship with a young Hungarian refugee causes her to see the war and her own world differently.
Keywords: World War, 1939-1945 -- Fiction -- United States; World War, 1939-1945 -- Fiction -- United States; Friendship -- Fiction; Refugees -- Fiction; Beaches -- Fiction